Method for manufacturing a zirconia sintered body
A three-stage heating process with controlled heating rates and temperatures for zirconia bodies with varying stabilizer content addresses the issue of visible stripes, ensuring high-quality zirconia sintered bodies are produced efficiently.
Patent Information
- Application Number
- KR1020237005295
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-25
- Filing Date
- 2021-09-24
- Publication Date
- 2026-11-05
- Estimated Expiration
- 2041-09-24
AI Technical Summary
Conventional short-time firing schedules for zirconia dental prostheses result in visible stripes between layers with different yttria content, compromising the color tone and strength of the sintered body.
A three-stage heating process with specific heating rates and temperature ranges is applied to a zirconia molded body or plastic body with varying stabilizer content, ensuring no visible stripes and maintaining the color tone and strength comparable to traditional long-time firing.
The method achieves a zirconia sintered body with no visible stripes and equivalent color tone and strength to traditional methods, despite being fired in a significantly shorter time.
Smart Images

Figure 112023017267136-PCT00009_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a zirconia sintered body. Background Technology
[0002] Traditionally, metal has been widely used for dental products (e.g., prosthetics such as crowns, crowns, and dentures, as well as orthodontic products and dental implant products). However, metal has the drawback of lacking aesthetics because its color is distinctly different from natural teeth, and there have also been cases where allergies were caused by the leaching of the metal. Therefore, to solve the problems associated with the use of metal, ceramic materials such as aluminum oxide (alumina) and zirconium oxide (zirconia) have been used in dental products as substitutes for metal. In particular, zirconia has excellent strength and relatively good aesthetics, so demand is rising along with the reduction in price.
[0003] Meanwhile, in order to produce dental prostheses using zirconia, a block or disc-shaped workpiece (workpiece to be cut) is pre-sintered at a temperature 400 to 700°C lower than the temperature at which an ideal sintered body is obtained, and the shape of the dental prosthesis is cut using CAD / CAM equipment. Since the cut unsintered zirconia workpiece is held at a maximum temperature of 1400°C to 1650°C and then sintered, the total time required for heating, holding, and cooling is typically 6 to 12 hours. Regarding this time, there has recently been an increasing demand for short-time firing, and firing furnaces capable of short-time firing as described in Patent Documents 1 and 2 are also being manufactured.
[0004] In addition, recently, in order to achieve both strength and aesthetics in dental prostheses using zirconia, there is an increasing number of cutting workpieces, so-called yttria multizirconia blanks, having multiple layers with different contents of a stabilizer (e.g., yttria) (see, for example, Patent Document 3, etc.). Prior art literature
[0005] Japanese Patent Publication No. 2015-531048, Japanese Patent Publication No. 2019-524298, International Publication No. 2020 / 138316 The problem to be solved
[0006] Patent documents 1 to 3 disclose a firing furnace and schedule conditions for firing ceramics containing zirconia in a short time. However, as a result of the inventors' investigation, it was found that when a conventional short-time firing schedule is used, while the color tone and strength of an ideal dental prosthesis are obtained in the obtained sintered body, there is a problem in that stripes occur between layers with different content of yttria, a stabilizer.
[0007] Therefore, the present invention aims to provide a method for manufacturing a zirconia sintered body in which a zirconia molded body or a zirconia plastic body having multiple layers with different amounts of stabilizers is sintered in a short time, and no streaks are visible between the layers with different amounts of stabilizers. In addition, the invention aims to provide a method for manufacturing a zirconia sintered body that can reproduce the color tone and strength of an ideal dental prosthesis to the same extent as when fired under normal conditions, despite sintering the zirconia molded body or a zirconia plastic body in a short time. means of solving the problem
[0008] The inventors, having conducted extensive research to solve the above problem, discovered that by using a specific short-time firing schedule on a zirconia molded body or a zirconia plastic body having multiple layers with different amounts of stabilizers, a zirconia sintered body in which no streaks are visible between the layers can be obtained even with short-time firing. Based on this finding, they further conducted research and came to complete the present invention.
[0009] That is, the present invention includes the following inventions.
[0010] [1] A firing process for firing a zirconia molded body or a zirconia plastic,
[0011] The above zirconia molded body or zirconia plastic body comprises a plurality of layers containing a stabilizer, and
[0012] The above plurality of layers includes layers with different contents of a stabilizer, and
[0013] The above firing process comprises at least three stages of a heating process, including a first heating process (H1), a second heating process (H2), and a third heating process (H3), and
[0014] The heating rate of the second heating process (H2) is HR2,
[0015] When the heating rate of the third heating process (H3) is set to HR3,
[0016] HR2 = greater than 0 ℃ / min and less than 50 ℃ / min,
[0017] HR3 = 5 ℃ / min or more and 150 ℃ / min or less,
[0018] HR3 / HR2 > 1 and,
[0019] The starting temperature in each heating process is
[0020] At H1, 1000 ℃ or less,
[0021] In H2, greater than 1250 ℃ and less than or equal to 1450 ℃,
[0022] In H3, it is 1450 ℃ or higher and 1550 ℃ or lower, and
[0023] The temperature reached in each heating process is
[0024] In H1, greater than 1250 ℃ and less than or equal to 1450 ℃,
[0025] In H2, 1450 ℃ or higher and 1550 ℃ or lower,
[0026] A method for manufacturing a zirconia sintered body, wherein the temperature in H3 is 1500 ℃ or higher and 1750 ℃ or lower.
[0027] [2] A method for manufacturing a zirconia sintered body as described in [1], wherein the heating rate of the first heating process (H1) above is HR1, and HR1 is 40 to 500 ℃ / min.
[0028] [3] A method for manufacturing a zirconia sintered body as described in [1] or [2], wherein the difference in the content of the stabilizer between layers with different content of the stabilizer is 0.1 mol% or more.
[0029] [4] A method for manufacturing a zirconia sintered body as described in any one of [1] to [3], wherein the above-mentioned stabilizer is yttria.
[0030] [5] A method for manufacturing a zirconia sintered body as described in [4], wherein the content of yttria in all layers of the plurality of layers is 2.5 mol% or more and 7.5 mol% or less relative to the total mol of zirconia and yttria.
[0031] [6] A method for manufacturing a zirconia sintered body as described in any one of [1] to [5], wherein HR2 is 2 to 30 ℃ / min.
[0032] [7] A method for manufacturing a zirconia sintered body as described in any one of [1] to [6], wherein HR3 is 10 to 100 ℃ / min.
[0033] [8] A method for manufacturing a zirconia sintered body as described in any one of [1] to [7], with HR3 / HR2 > 1.5.
[0034] [9] A method for manufacturing a zirconia sintered body as described in any one of [1] to [8], wherein the maximum firing temperature in the above heating process is 1400 to 1750 ℃ and the holding time at the maximum firing temperature is within 30 minutes.
[0035]
[10] A method for manufacturing a zirconia sintered body as described in [9], which further includes a cooling process, wherein the cooling rate from the highest firing temperature in the cooling process to 800 ℃ is 10 ℃ / min or more.
[0036]
[11] A method for manufacturing a zirconia sintered body as described in any one of [1] to
[10] , wherein the total sintering time from the start of the first heating process (H1) in the above sintering process to the end of the holding time at the maximum sintering temperature is within 120 minutes.
[0037]
[12] A method for manufacturing a zirconia sintered body as described in any one of [1] to
[11] , wherein 55% or more of the zirconia molded body or zirconia plastic body is monoclinic.
[0038]
[13] A method for manufacturing a zirconia sintered body as described in any one of [1] to
[12] , wherein at least a portion of the stabilizer is not incorporated into the zirconia in the above-mentioned zirconia molded body or zirconia plastic body.
[0039]
[14] A method for manufacturing a zirconia sintered body as described in any one of [1] to
[13] , wherein the above zirconia molded body or zirconia plastic body has a predetermined shape for a dental product.
[0040]
[15] A method for manufacturing a zirconia sintered body as described in
[14] , the above dental product being a dental prosthesis. Effects of the invention
[0041] According to the method for manufacturing a zirconia sintered body of the present invention, a method for manufacturing a zirconia sintered body can be provided in which a zirconia molded body or a zirconia plastic body having a plurality of layers with different amounts of stabilizers is sintered in a short time, and stripes between layers with different amounts of stabilizers are not visible. In addition, a method for manufacturing a zirconia sintered body can be provided in which, despite being sintered in a short time, the color tone and strength of an ideal dental prosthesis can be reproduced to the same extent as when sintered under normal sintering conditions (total sintering time: 6 to 12 hours). Brief explanation of the drawing
[0042] FIG. 1 shows a schematic diagram of a zirconia plastic related to the present invention. Specific details for implementing the invention
[0043] Although it is not certain why a zirconia sintered body is obtained in which no streaks occur between layers with different amounts of stabilizers by using the method for manufacturing a zirconia sintered body of the present invention, by sintering a zirconia molded body or a zirconia plastic body in a short time (e.g., total sintering time of 120 minutes or less), the inventors estimate as follows. First, regarding the zirconia sintered body obtained, it is thought that the greater the difference in light transmittance (hereinafter referred to as △L(WB)) between adjacent layers with different amounts of stabilizers, the more clearly streaks are visible due to short-time sintering, and conversely, if the difference in △L(WB) is small, streaks are less visible.
[0044] While examining countermeasures, the inventors discovered a phenomenon in which, when short-term firing is performed, the temperature range in which the rate of increase of ΔL(WB) changes as the temperature rises varies depending on the amount of stabilizer included in the layer. From this phenomenon, it is believed that a zirconia sintered body is obtained in which stripes are not visible, that is, the stacking interface is not clearly discernible, because the sintering time is short, and the zirconia sintered body is obtained in which stripes are not visible, that is, the stacking interface is not clearly discernible. This is because the difference in ΔL(WB) between adjacent layers with different amounts of stabilizers is suppressed by slowing down the heating rate in a specific temperature range where the difference in ΔL(WB) between layers is difficult to make, while increasing the ΔL(WB) of the entire zirconia molded body or zirconia plastic body to be heated, and the heating rate in a temperature range where the difference in ΔL(WB) is likely to make is increased, and the difference in ΔL(WB) between layers with different amounts of stabilizers is suppressed.
[0045] The present invention will be described in detail below.
[0046] The firing furnace used for firing according to the present invention is an atmospheric furnace, and may be a box furnace, crucible furnace, tubular furnace, furnace bottom lifting furnace, continuous furnace, or rotary kiln; may also be a resistance heating furnace, induction heating furnace, direct current type electric furnace, IH furnace, high frequency furnace, or microwave furnace; may use a metal heating element, silicon carbide, molybdenum disilicide, lanthanum chromite, molybdenum, carbon, tungsten, etc. as the heating element, and may use SiC as the heating element susceptor. It may also be a firing furnace that combines two or more of these. Furthermore, the internal volume of the firing furnace, which has a support for holding a zirconia molded body or a zirconia plastic body having a predetermined shape such as a crown, is smaller, so that the thermal efficiency is good and it is easy to maintain the heat amount inside the furnace during firing.
[0047] The zirconia molded body in the present invention is a molded body made of non-sintered zirconia, that is, zirconia that has not been sintered. The zirconia molded body in the present invention may be partially stabilized zirconia or fully stabilized zirconia. In the present invention, "not sintered" refers to a state in which the parts of the zirconia powder particles in contact with each other are not reacting with one another. The zirconia plastic of the present invention may serve as a precursor (intermediate product) of a zirconia sintered body. A zirconia plastic refers, for example, to a block formed from zirconia particles (powder) in a state in which they are not completely sintered. Furthermore, in this specification, the upper and lower limits of numerical ranges (heating rate, cooling rate, firing time, temperature, rate ratio, content of each component (e.g., stabilizer), etc.) may be appropriately combined.
[0048] The method for manufacturing a zirconia sintered body according to the present invention comprises at least three heating steps. For each heating step, the first heating step is denoted as H1, the second heating step as H2, and the third heating step as H3, and each heating step has a different heating rate. Additionally, the heating steps may consist of only three steps, or may include other heating steps.
[0049] [First Heating Process (H1)]
[0050] In the first heating process (H1) of the method for manufacturing a zirconia sintered body according to the present invention, the zirconia molded body or zirconia plastic body is heated in a firing furnace heated to room temperature or above room temperature up to 1000°C in one go to reach the temperature of the first heating process (H1). It is preferable that the zirconia molded body or zirconia plastic body prior to firing in the first heating process (H1) has a predetermined shape of a dental product. Examples of dental products include dental prostheses such as typical crowns, crowns, and dentures; orthodontic products; and dental implant products. The zirconia molded body or zirconia plastic body prior to heating may be processed using a dental CAD / CAM device or may be manufactured by a dental technician by cutting or machining.
[0051] The zirconia molded body or zirconia plastic body prior to heating may be placed directly on the muffle member of the firing furnace during firing, placed inside the furnace using a tray, support, or pin made of ceramic or high-melting-point metal, or placed using ceramic beads.
[0052] The starting temperature of the first heating process (H1) is not particularly limited as long as it is 1000°C or lower, but is preferably room temperature to 1000°C, more preferably room temperature to 450°C, even more preferably room temperature to 400°C, and particularly preferably room temperature to 300°C. The temperature reached in the first heating process (H1) is 1250°C to 1450°C, and is preferably 1300°C or higher in that the working time can be shortened, more preferably 1350°C or higher in that the difference in transparency between layers with different content of the stabilizer yttria can be reduced, and even more preferably 1400°C or higher.
[0053] In addition, when the heating rate of the first heating process (H1) is set to HR1, HR1 is preferably 40 ℃ / min or higher, more preferably 50 ℃ / min or higher, even more preferably 60 ℃ / min or higher, and particularly preferably 70 ℃ / min or higher, in order to further shorten the working time. Also, HR1 is preferably 500 ℃ / min or lower, more preferably 450 ℃ / min or lower, even more preferably 400 ℃ / min, and particularly preferably 350 ℃ / min or lower. If HR1 exceeds 500 ℃ / min, there is a risk of causing cracks or fissures during firing. If the zirconia molded body or zirconia plastic body provided to the first heating process (H1) contains moisture used during processing or a color liquid for coloring, the first heating process (H1) may be initiated after undergoing a drying process at 300°C or lower for 1 minute or more and 20 minutes or less, preferably 5 minutes or more and 15 minutes or less. In addition, as a preferred embodiment, a method for manufacturing a zirconia sintered body in which HR1 / HR3 > 1 may be cited. HR1 / HR3 > 1.5 is more preferred, and HR1 / HR3 > 2 is even more preferred.
[0054] [Second Heating Process (H2)]
[0055] In the method for manufacturing a zirconia sintered body according to the present invention, when the heating rate of the second heating process (H2) is set to HR2, HR2 is greater than 0 ℃ / min and, in order to further shorten the working time, is preferably 1 ℃ / min or more, more preferably 2 ℃ / min or more, even more preferably 3 ℃ / min or more, and particularly preferably 4 ℃ / min or more. In addition, HR2 is less than 50 ℃ / min and, in order to better lightness and transparency of the obtained zirconia sintered body and to suppress the occurrence of streaks between layers with different yttria content, is preferably less than 40 ℃ / min, more preferably 35 ℃ / min or less, even more preferably 30 ℃ / min or less, and particularly preferably 20 ℃ / min or less.
[0056] The starting temperature of the second heating process (H2) is 1250 to 1450°C, and is preferably 1300°C or higher in that the working time can be shortened further, and is more preferably 1350°C or higher in that the difference in transparency between layers with different content of the stabilizer yttria can be reduced, and even more preferably 1400°C or higher. The temperature reached of the second heating process (H2) is 1450 to 1550°C, and is preferably 1470°C or higher in that the working time can be shortened further, more preferably 1490°C or higher, and even more preferably 1500°C or higher. In addition, the H2 reaching temperature is preferably 1540°C or lower, more preferably 1530°C or lower, and even more preferably 1520°C or lower, in that the brightness, lightness, and saturation of the zirconia sintered body obtained are superior, the color development of the composite oxide is superior when the zirconia molded body or zirconia plastic body contains the composite oxide, and the occurrence of streaks between layers with different yttria content is suppressed.
[0057] [Third Heating Process (H3)]
[0058] When the heating rate of the third heating process (H3) is set to HR3, in the case where a zirconia molded body or a zirconia plastic body having layers with different amounts of stabilizers is used for short-time firing, the difference in transparency between layers with different amounts of yttria, which is a stabilizer, can be reduced and the occurrence of streaks between layers with different amounts of yttria can be suppressed, so HR3 / HR2 > 1, and the brightness, lightness, and saturation of the zirconia sintered body obtained are superior, and when the zirconia molded body or zirconia plastic body contains a composite oxide, the color development of the composite oxide is superior and the occurrence of streaks between layers with different amounts of yttria can be further suppressed, so preferably HR3 / HR2 > 1.2, more preferably HR3 / HR2 > 1.5, and even more preferably HR3 / HR2 > 2. In addition, HR3 is 5 ℃ / min or more, and in terms of further shortening the processing time and suppressing the occurrence of streaks between layers with different yttria content, it is preferably 8 ℃ / min or more, more preferably 9 ℃ / min or more, and even more preferably 10 ℃ / min or more. In addition, HR3 is 150 ℃ / min or less, preferably 100 ℃ / min or less, and more preferably 50 ℃ / min or less, in terms of having better color saturation of the obtained zirconia sintered body, excellent color development of the composite oxide when the zirconia molded body or zirconia plastic body contains the composite oxide, and suppression of streak occurrence.
[0059] The starting temperature of the third heating process (H3) is 1450 to 1550°C, and in order to further shorten the working time and suppress the occurrence of streaks between layers with different yttria content, it is preferably 1470°C or higher, more preferably 1490°C or higher, and even more preferably 1500°C or higher. In addition, the starting temperature of H3 is preferably 1540°C or lower, more preferably 1530°C or lower, and even more preferably 1520°C or lower, in order to better obtain the lightness, lightness, and saturation of the zirconia sintered body and to better obtain the color development of the composite oxide when the zirconia molded body or zirconia plastic body contains the composite oxide.
[0060] The temperature reached in the third heating process (H3) is 1500 to 1750°C, and is preferably 1510°C or higher, more preferably 1530°C or higher, and even more preferably 1550°C or higher, in that the brightness, lightness, and saturation of the zirconia sintered body obtained are superior, and the color development of the composite oxide is superior when the zirconia molded body or zirconia plastic body contains the composite oxide. In addition, the temperature reached in H3 is preferably 1700°C or lower, more preferably 1650°C or lower, and even more preferably 1600°C or lower, in that the working time can be shortened further, the brightness, lightness, and saturation of the zirconia sintered body obtained are superior, the color development of the composite oxide is superior when the zirconia molded body or zirconia plastic body contains the composite oxide is superior, and the occurrence of streaks between layers with different yttria content is suppressed.
[0061] As for the zirconia molded body or zirconia plastic used in the method for manufacturing a zirconia sintered body of the present invention, it is preferable that, in addition to zirconia, it comprises a stabilizer capable of suppressing the phase transition of zirconia. As for the zirconia molded body or zirconia plastic, it is preferable that the zirconia molded body or zirconia plastic is one in which at least a portion of the stabilizer is not dissolved in zirconia. It is preferable that the stabilizer is capable of forming partially stabilized zirconia.
[0062] The zirconia molded body or zirconia plastic body used in the method for manufacturing a zirconia sintered body of the present invention comprises a plurality of layers containing a stabilizer, wherein the plurality of layers comprises layers with different amounts of the stabilizer relative to the total mol of zirconia and the stabilizer. The number of layers with different amounts of the stabilizer is not particularly limited as long as there are two or more layers, and may be three, four, five, or six layers. Furthermore, the zirconia molded body or zirconia plastic body may have layers with different amounts of the stabilizer, and may also include two or more layers with the same amount of the stabilizer. By having layers with different amounts of the stabilizer in the zirconia molded body or zirconia plastic body, it becomes possible to appropriately set the transparency or strength required by a specific part (layer) within a single material for the zirconia sintered body obtained by short-time firing. In addition, the difference in the content of the stabilizer between layers with different stabilizer contents is preferably 0.1 mol% or more, and from the perspective of achieving translucency and strength desirable for dental use, it is more preferable that it is 0.3 mol% or more, and even more preferable that it is 0.5 mol% or more. Furthermore, the difference in the content of the stabilizer between layers with different stabilizer contents is preferably 3 mol% or less, and from the perspective of achieving translucency and strength desirable for dental use, it is more preferable that it is 2.5 mol% or less, and even more preferable that it is 2 mol% or less.
[0063] In the zirconia molded body or zirconia plastic body used in the method for manufacturing a zirconia sintered body of the present invention, from the perspective of achieving translucency and strength desirable for dental use, it is desirable that the trend of increase or decrease in the content of the stabilizer (preferably yttria) relative to the total mol of zirconia and stabilizer does not change along a straight line extending from one end to the other end of the zirconia plastic body. In other words, it is desirable that the content of the stabilizer (preferably yttria) increases or decreases monotonically. Hereinafter, the zirconia plastic body will be explained using FIG. 1 as a schematic diagram. In the straight line extending from one end (P) to the other end (Q) of the zirconia plastic body (10) of FIG. 1, it is desirable that the trend of increase or decrease in the content of the stabilizer does not change in the reverse direction. That is, in the case where the content of the stabilizer tends to decrease along a straight line from one end (P) to the other end (Q), it is desirable that there is no section where the content of the stabilizer substantially increases.
[0064] The above stabilizers include, for example, calcium oxide (CaO), magnesium oxide (MgO), yttria, cerium oxide (CeO2), scandium oxide (Sc2O3), niobium oxide (Nb2O5), lanthanum oxide (La2O3), erbium oxide (Er2O3), and praseodymium oxide (Pr6O2). 11Examples of oxides include (sm2O3), samarium oxide (Sm2O3), europium oxide (Eu2O3), and thulium oxide (Tm2O3). One type of stabilizer may be used alone, or two or more types may be used in combination. The content of the stabilizer in the zirconia plastic and the sintered body of the present invention can be measured, for example, by inductively coupled plasma (ICP) emission spectroscopy, fluorescence X-ray analysis, etc. In the zirconia plastic and the sintered body of the present invention, the content of the stabilizer is preferably 0.1 to 18 mol% with respect to the total mol of zirconia and the stabilizer, more preferably 1 to 15 mol%, and even more preferably 2 to 8 mol%. From the perspective of the strength and transparency of the obtained zirconia sintered body, it is preferable that the zirconia molded body or the zirconia plastic includes yttria as a stabilizer. In all layers of the plurality of layers having a zirconia molded body or a zirconia plastic body, the yttria content is preferably 2.5 mol% or more, more preferably 3 mol% or more, even more preferably 3.5 mol% or more, and particularly preferably 3.8 mol% or more with respect to the total mol of zirconia and yttria. When the yttria content is 2.5 mol% or more, the light transmittance of the zirconia sintered body can be increased. In addition, in all layers of the plurality of layers, the yttria content is preferably 7.5 mol% or less, more preferably 7.0 mol% or less, even more preferably 6.5 mol% or less, and particularly preferably 6.0 mol% or less with respect to the total mol of zirconia and yttria. When the yttria content is 7.5 mol% or less, the decrease in strength of the obtained zirconia sintered body can be suppressed.In one preferred embodiment (X-1), a plurality of layers containing yttria as a stabilizer contained in a zirconia molded body or a zirconia plastic body are provided, wherein the plurality of layers include two or more layers with different yttria content ratios, and the layer with the highest yttria content ratio (Y. H The yttria content in ) is 3.5 mol% or more and 7.5 mol% or less, and the layer with the lowest yttria content (Y L The yttria content in ) is 2.5 mol% or more and 7.0 mol% or less, and the layer (Y H Yttria content / layer (Y) in ) L A method for manufacturing a zirconia sintered body satisfying the yttria content > 1 in ) can be cited. In the above preferred embodiment (X-1), the layer (Y) with the highest yttria content H The yttria content in ) is 3.8 mol% or more and 7.5 mol% or less, and also the layer with the lowest yttria content (Y L It is more preferable that the yttria content in ) is 3.0 mol% or more and 6.5 mol% or less, and the layer with the highest yttria content (Y H The yttria content in ) is 3.8 mol% or more and 7.0 mol% or less, and also the layer with the lowest yttria content (Y L It is more preferable that the yttria content in ) is 3.0 mol% or more and 6.0 mol% or less.
[0065] In the zirconia molded body or zirconia plastic of the present invention, it is preferable that at least a portion of the stabilizer is not dissolved in the zirconia. That a portion of the stabilizer is not dissolved in the zirconia can be confirmed, for example, by an XRD pattern. If a peak originating from the stabilizer is identified in the XRD pattern of the zirconia plastic, it indicates that there is a stabilizer in the zirconia molded body or zirconia plastic that is not dissolved in the zirconia. If the entire amount of the stabilizer is dissolved, a peak originating from the stabilizer is basically not identified in the XRD pattern. However, depending on conditions such as the crystal state of the stabilizer, there may be cases where the stabilizer is not dissolved in the zirconia even if a peak of the stabilizer is not present in the XRD pattern. If the main crystal system of the zirconia is tetragonal and / or cubic and a peak of the stabilizer is not present in the XRD pattern, it is considered that most, or basically all, of the stabilizer is dissolved in the zirconia. In the zirconia molded body or zirconia plastic of the present invention, the entire stabilizer does not need to be dissolved in the zirconia. Furthermore, in the present invention, the fact that the stabilizer is dissolved means, for example, that an element (atom) included in the stabilizer is dissolved in the zirconia.
[0066] In the zirconia molded body or zirconia plastic body of the present invention, the presence rate f of yttria not dissolved in zirconia (hereinafter referred to as "undissolved yttria") y It can be calculated based on the following formula (1). The abundance of unused yttria f y It is desirable that it be greater than 0%, more desirable that it be 1% or more, even more desirable that it be 2% or more, and particularly desirable that it be 3% or more. Presence rate f of undissolved yttria yThe upper limit of may be, for example, 15% or less, but preferably depends on the yttria content in the zirconia molded body or zirconia plastic. When the yttria content is 2.5 mol% or more and less than 4.5 mol%, f y can be 7% or less. When the yttria content is 4.5 mol% or more and less than 5.8 mol%, f y can be 11% or less. When the yttria content is 5.8 mol% or more and less than 7.5 mol%, f y It can be 15% or less.
[0067] In the zirconia molded body or zirconia plastic of the present invention, when the yttria content is 2.5 mol% or more and less than 4.5 mol%, f y 0.5% or more is preferable, 1.0% or more is more preferable, and 2.0% or more is even more preferable. When the yttria content is 4.5 mol% or more and less than 5.8 mol%, the presence rate f of undissolved yttria is y is preferably 1% or more, more preferably 2% or more, and even more preferably 3% or more. When the yttria content is 5.8 mol% or more and 7.5 mol% or less, f y is preferably 2% or more, more preferably 3% or more, and even more preferably 4% or more. In the zirconia plastic of the present invention, when the yttria content is 2.5 mol% or more and less than 4.5 mol%, f m / f y is preferably 20 to 200, more preferably 25 to 100, and even more preferably 30 to 60. When the yttria content is 4.5 mol% or more and less than 5.8 mol%, f m / f y5 to 45 is preferable, 10 to 40 is more preferable, and 15 to 35 is even more preferable. When the yttria content is 5.8 mol% or more and 7.5 mol% or less, f m / f y 2 to 40 is preferable, 5 to 35 is more preferable, and 10 to 30 is even more preferable.
[0068]
[0069] In formula (1), I y (111) represents the peak intensity of the (111) plane of yttria near 2θ = 29° in the XRD pattern by CuKα line. I m (111) and I m (11-1) represents the peak intensity of the (111) plane and (11-1) plane of the monoclinic zirconia. I t (111) represents the peak intensity of the (111) plane of the tetragonal system of zirconia. I c (111) represents the peak intensity of the (111) plane of the cubic system of zirconia.
[0070] The above formula (1) is, I y (111) By substituting a different peak instead, it can also be applied to the calculation of the undissolved presence of stabilizers other than yttria.
[0071] In the zirconia molded body or zirconia plastic body of the present invention, it is preferable that the main crystal system of the zirconia is monoclinic. In the present invention, "the main crystal system is monoclinic" means that the ratio f of the monoclinic system in zirconia calculated by the following formula (2) to the total amount of all crystal systems (monoclinic, tetragonal, and cubic) in zirconia m This refers to a ratio of 50% or more. In the zirconia molded body or zirconia plastic body of the present invention, the ratio of monoclinic zirconia in the zirconia calculated by the following formula (2) is fm Regarding the total amount of monoclinic, tetragonal, and cubic crystals, 55% or more is preferable, 60% or more is more preferable, 70% or more is even more preferable, 75% or more is even more preferable, 80% or more is particularly preferable, 85% or more is even more particularly preferable, and 90% or more is most preferable. The proportion of monoclinic crystals f m It can be calculated from the following formula (2) based on the peaks of the X-ray diffraction (XRD) pattern by CuKα rays. In addition, the main crystal system in the zirconia molded body or zirconia plastic body may contribute to the increase in shrinkage temperature and the reduction in firing time.
[0072] In the zirconia molded body or zirconia plastic of the present invention, tetragonal and cubic peaks do not need to be substantially detected. That is, the proportion of monoclinic peaks f m It can be made 100%.
[0073]
[0074] In formula (2), I m (111) and I m (11-1) represents the peak intensities of the (111) plane and (11-1) plane of the monoclinic zirconia, respectively. I t (111) represents the peak intensity of the (111) plane of the tetragonal system of zirconia. I c (111) represents the peak intensity of the (111) plane of the cubic system of zirconia.
[0075] The zirconia molded body or zirconia plastic body may include additives as needed. Examples of additives include binders, coloring agents (including pigments, complex pigments, and fluorescent agents), alumina (Al2O3), titanium oxide (TiO2), silica (SiO2), etc. The additives may be used as a single type or as a mixture of two or more types.
[0076] Examples of the above binders include polyvinyl alcohol, methylcellulose, carboxymethylcellulose, acrylic binders, wax binders (paraffin wax, etc.), polyvinyl butyral, polymethyl methacrylate, ethyl cellulose, polyethylene, polypropylene, ethylene vinyl acetate copolymer, polystyrene, atactic polypropylene, methacrylate resin, stearic acid, etc.
[0077] The above pigment may be, for example, an oxide of at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, Tb, and Er (specifically, NiO, Cr2O3, etc.), an oxide of at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Pr, Sm, Eu, Gd, and Tb is preferred, and an oxide of at least one element selected from the group consisting of Ti, V, Cr, Mn, Fe, Co, Ni, Zn, Y, Zr, Sn, Sb, Bi, Ce, Sm, Eu, Gd, and Tb is more preferred. In addition, the zirconia molded body or zirconia plastic of the present invention may not include erbium oxide (Er2O3). Examples of the composite pigments include (Zr,V)O2, Fe(Fe,Cr)2O4, and (Ni,Co,Fe)(Fe,Cr)2O4·ZrSiO 4,Examples of complex oxides include (Co,Zn)Al2O4. Examples of fluorescent agents include, for instance, Y2SiO5:Ce, Y2SiO5:Tb, (Y,Gd,Eu)BO3, Y2O3:Eu, YAG:Ce, ZnGa2O4:Zn, and BaMgAl. 10 O 17 Examples include :Eu, etc.
[0078] The method for manufacturing the zirconia molded body used in the present invention is not particularly limited, but examples include a manufacturing method comprising a process of press-molding a mixed powder consisting of zirconia (preferably, zirconia powder having a monoclinic crystal system as the main crystal system) and the above-mentioned stabilizer at a pressure of 175 MPa or more to obtain a zirconia molded body. By press-molding at the above pressure, the bulk density of the zirconia molded body (and subsequently the obtained zirconia sintered body) can be increased regardless of thickness. Furthermore, in this specification, the above-mentioned pressure of 175 MPa or more refers to the maximum pressure during press-molding.
[0079] The method for manufacturing the zirconia plastic used in the present invention is not particularly limited, but examples include a method of manufacturing a zirconia molded body formed from raw material powder containing zirconia particles (preferably zirconia particles whose main crystal system is monoclinic) and a stabilizer, and firing (i.e., plasticizing) the zirconia particles at a temperature at which the zirconia particles do not reach sintering. The method for manufacturing the zirconia molded body is as described above. An example of the method for manufacturing the zirconia plastic of the present invention is described. First, raw material powder for the zirconia molded body is prepared. A mixture is prepared using monoclinic zirconia powder and a stabilizer powder (e.g., yttria powder) to achieve a desired content of the stabilizer (e.g., yttria). Next, this mixture is added to water to prepare a slurry, and wet-grinded and mixed using a ball mill until a desired particle size is achieved. The slurry after grinding is dried with a spray dryer to form granules. The obtained powder is calcined at a temperature where the zirconia particles do not reach sintering (e.g., 800 to 1200°C) to produce a powder (primary powder). Pigment may be added to the primary powder. Subsequently, the primary powder is added to water to produce a slurry, and wet-grinded and mixed using a ball mill until the desired particle size is achieved. After grinding, additives such as a binder are added to the slurry as needed, and then dried with a spray dryer to produce a mixed powder (secondary powder). The secondary powder is filled into a predetermined mold, the upper surface is rubbed to flatten it, the upper mold is set, and the secondary powder is press-molded using a single-axis press molding machine to obtain a zirconia molded body. As described above, the pressure when press-molding the mixed powder is preferably 175 MPa or higher. Additionally, the obtained zirconia molded body may or may not be further subjected to CIP (Cold Isostatic Press) molding.
[0080] The zirconia molded body or zirconia plastic body may have a multilayer structure. When manufacturing a zirconia plastic body with a multilayer structure, in order to make the zirconia molded body into a multilayer structure, the primary powder in the above manufacturing method may be divided into at least two (preferably four) parts.
[0081] The density of the zirconia plastic is preferably 2.7 g / cm³ or higher. In addition, the density of the zirconia plastic is preferably 4.0 g / cm³ or lower, more preferably 3.8 g / cm³ or lower, and even more preferably 3.6 g / cm³ or lower. Within this density range, molding processing can be easily performed. Density can be calculated, for example, as (mass of plastic) / (volume of plastic).
[0082] In addition, the three-point bending strength of the zirconia plastic is preferably 15 to 70 MPa, more preferably 18 to 60 MPa, even more preferably 20 to 50 MPa, and particularly preferably 20 to 40 MPa. The above bending strength can be measured in accordance with ISO 6872:2015, but by changing only the condition of the specimen size, the measurement is performed using a specimen of size 5 mm × 10 mm × 50 mm. The surface and surface C of the specimen are finished in the longitudinal direction with 600-grit sandpaper. The specimen is positioned so that the widest surface faces the vertical direction (load direction). For the bending test measurement, the span is 30 mm and the crosshead speed is 0.5 mm / min.
[0083] Next, the zirconia molded body obtained as described above is calcined to obtain a zirconia plastic body. The calcination temperature is, for example, preferably 800°C or higher, more preferably 900°C or higher, and even more preferably 950°C or higher. In addition, to increase dimensional accuracy, the calcination temperature is, for example, preferably 1200°C or lower, more preferably 1150°C or lower, and even more preferably 1100°C or lower. It is believed that at such calcination temperatures, the solid solution of the stabilizer does not proceed.
[0084] In the method for manufacturing a zirconia sintered body according to the present invention, as long as the relationship between the starting temperature, the temperature reached, the heating rate range, and HR3 / HR2 > 1 of each of the above-mentioned heating processes is satisfied, the heating rate of each of the above-mentioned heating processes may be constant or may be changed midway to be multi-stage. For example, in one embodiment, for the second heating process, the temperature may be raised at 50 ℃ / min for 30 seconds from the starting temperature, and after 30 seconds, the temperature may be raised at 10 ℃ / min. In another embodiment, for the third heating process, the temperature may be raised at 50 ℃ / min for 30 seconds from the starting temperature, and after 30 seconds, the temperature may be raised at 10 ℃ / min.
[0085] [Maintenance Process]
[0086] In the method for manufacturing a zirconia sintered body according to the present invention, the holding time at the maximum reached temperature (maximum firing temperature) is preferably within 30 minutes, and in terms of further shortening the working time, it is more preferably 10 to 25 minutes, and even more preferably 15 to 20 minutes. In addition, the maximum firing temperature is preferably 1400 to 1750°C, and in terms of the brightness, lightness, and saturation of the zirconia sintered body obtained being superior, and the color development of the composite oxide being superior when the zirconia molded body or zirconia plastic body contains the composite oxide, it is preferably 1510°C or higher, more preferably 1530°C or higher, and even more preferably 1550°C or higher. In addition, the maximum firing temperature is preferably 1750°C or lower, more preferably 1650°C or lower, and even more preferably 1600°C or lower, in order to further shorten the processing time, provide superior brightness, translucency, and saturation of the obtained zirconia sintered body, provide superior color development of the composite oxide when the zirconia molded body or zirconia plastic body contains the composite oxide, and suppress the occurrence of streaks between layers with different yttria content. The holding process is preferably performed immediately after the third heating process, but as long as the effects of the present invention are exhibited, another heating process may be performed between the third heating process and the holding process. In embodiments that do not include heating processes other than those mentioned above, the temperature reached by H3 becomes the maximum firing temperature.
[0087] In the firing process, the total firing time from the start of the first heating process to the end of the holding time at the highest firing temperature is preferably within 120 minutes, more preferably within 90 minutes, and even more preferably within 75 minutes, in order to further shorten the working time.
[0088] [Cooling Process (Temperature Reduction Process)]
[0089] In the method for manufacturing a zirconia sintered body according to the present invention, it is preferable to include a process of cooling after maintaining the maximum firing temperature for a predetermined time. In the cooling process, the cooling rate from the maximum firing temperature in the heating process to 800°C is preferably 10°C / min or more, more preferably 30°C / min or more, and even more preferably 50°C / min or more. The cooling method may use any or a combination of external air introduction cooling, water cooling, air cooling, slow cooling, and air cooling. The temperature reached during the cooling process varies depending on the type and performance of the firing furnace, and may be 950°C, 750°C, or 1000°C.
[0090] The color difference ΔE*ab of the zirconia sintered body obtained by the manufacturing method of the present invention is preferably 2.7 or less, more preferably 2.0 or less, even more preferably 1.6 or less, and particularly preferably 0.8 or less, in terms of being desirable as a dental product. The subject of comparative measurement for the color difference ΔE*ab is the color of the zirconia sintered body in the case of normal firing (total firing time: 6 to 12 hours). The method for evaluating color is as described in the examples below. Furthermore, in this specification, the "total firing time" (also referred to as total firing time) refers to the time from the start of the heating process of the first heating process in the firing process to the end of the holding time at the maximum firing temperature.
[0091] The difference between the lightness index L* of the zirconia sintered body obtained by the manufacturing method of the present invention and the lightness index L* of the zirconia sintered body obtained by normal firing (total firing time: 6 to 12 hours) is preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.0 or less, in terms of being desirable as a dental product. L*, a*, and b* of the zirconia sintered body obtained by the manufacturing method of the present invention can be selected and set according to the intended part, such as the cervical (dental part), body, and insulator (insulating part).
[0092] The present invention includes embodiments in which the above configuration is combined in various ways within the scope of the technical concept of the present invention, as long as the effects of the present invention are achieved.
[0093] Examples
[0094] Next, the present invention will be described more specifically with reference to examples, but the present invention is not limited in any way by these examples, and many modifications are possible by those skilled in the art within the scope of the technical concept of the present invention.
[0095] [Example 1]
[0096] [Production of raw material powder used in the production of zirconia plastics]
[0097] The method for preparing the raw material powder used to produce the zirconia plastic used in Example 1 is described. First, a mixture was prepared using monoclinic zirconia powder and yttria powder such that, excluding the coloring component, the composition was as described in Table 1. Next, this mixture was added to water to prepare a slurry, and wet-grinded and mixed using a ball mill until the average particle size was 0.13 μm or less. The slurry after grinding was dried with a spray dryer, and the obtained powder was calcined at a calcination temperature of 950 °C for 2 hours to produce a powder (primary powder). In addition, the above average particle size can be determined by the laser diffraction scattering method. Specifically, the laser diffraction scattering method can be measured on a volume basis using, for example, a laser diffraction type particle size distribution measuring device (SALD-2300: manufactured by Shimadzu Corporation) with a 0.2% aqueous sodium hexametaphosphate solution as a dispersion medium. In addition, the yttria content in Table 1 refers to the yttria content relative to the total mol of zirconia and yttria.
[0098] A coloring component was added to the obtained primary powder according to the composition listed in Table 1. Subsequently, the powder containing the coloring component was added to water to prepare a slurry, and wet-ground and mixed using a ball mill until the average particle size was 0.13 μm or less. After grinding, a binder was added to the slurry, and then dried with a spray dryer to produce a powder (secondary powder). The produced secondary powder was used as a raw material powder for the manufacture of the zirconia plastic described below.
[0099] [Fabrication of Zirconia Plastic Blocks]
[0100] Next, a method for manufacturing a block of zirconia plastic used to produce a crown-shaped zirconia sintered body is described. First, 15 g of the raw material powders listed in Table 1 were filled into a mold with inner dimensions of 20 mm × 25 mm, in the order of the first layer of raw material powder and then the second layer of raw material powder, and a first press molding was performed using a single-axis press molding machine at a surface pressure of 300 kg / cm² for 90 seconds. The obtained first press molded body (zirconia molded body) was CIP molded at 1700 kg / cm² for 5 minutes to produce a molded body with a layered structure. The obtained molded body was sintered at 1000°C for 2 hours to produce a block of zirconia plastic.
[0101] Using the obtained block of zirconia plastic, the shape was machined according to the evaluation of each characteristic described below, and sintering was performed according to the sintering schedule described in Table 2. The results of the evaluation of each characteristic are as described below. In addition, regarding the evaluation of ΔL(WB) of the zirconia sintered body, zirconia sintered bodies of each layer alone were fabricated and evaluated as described below.
[0102] [Examples 2–5, Comparative Example 1 and Reference Example 1]
[0103] A secondary powder was prepared in the same manner as in Example 1, and a block of a zirconia plastic was prepared. In addition, a zirconia sintered body was prepared in the same manner as in Example 1, except that the firing schedule was changed as described in Tables 2 and 3, and each characteristic was evaluated.
[0104] [Evaluation of ΔL(WB) of each layer of the zirconia sintered body]
[0105] For each of the zirconia sintered bodies of Examples 1 to 5, Comparative Example 1, and Reference Example 1, a zirconia sintered body consisting of the first layer and the second layer as described in Table 1 was prepared by the following method, and (L*, a*, b*) was measured using the L*a*b* color system (JIS Z 8781-4: 2013 Colorimetry - Part 4: CIE 1976 L*a*b* color space). In addition, ΔL(WB) obtained from each (L*, a*, b*) of the zirconia sintered body was calculated. ΔL(WB) can be obtained by the following formula (1) using the L value (L1*) of the zirconia sintered body measured against a white background and the L value (L2*) of the zirconia sintered body measured against a black background.
[0106]
[0107] First, a molded body consisting of raw powder in each layer was produced by press molding with a size adjusted in advance to obtain a zirconia sintered body with a thickness of 1.2 mm. Next, the molded body was sintered at 1000°C for 2 hours to produce a zirconia plastic. Using an InFire HTC speed (manufactured by Dentsply Silona, Inc.) as the sintering furnace, the zirconia plastic was sintered according to the sintering schedule shown in Tables 2 and 3 to produce a zirconia sintered body. Both sides of the obtained zirconia sintered body were polished with #600 abrasive paper to obtain a zirconia sintered body with a thickness of 1.2 mm. Then, using a dental colorimeter (7-band LED light source, Crystal Eye) (manufactured by Olympus Corporation), measurements were taken against a white background and a black background for each layer (n = 3). The average values of n = 3 are shown as evaluation results in Tables 2 and 3.
[0108] [Evaluation of the Aesthetics of Crown-Shaped Zirconia Sintered Bodies]
[0109] For the zirconia sintered bodies of each of Examples 1 to 5, Comparative Example 1, and Reference Example 1, the aesthetics were evaluated visually in comparison with the appearance of natural teeth using the following method. For the evaluation, a commercially available shade guide having an appearance equivalent to that of natural teeth may be used. Specifically, for example, the commercially available shade guide VITA Classical (trade name) manufactured by VITA Corporation can be cited. First, the obtained zirconia plastic block was machined into an anterior crown shape using a DWX-52DC (manufactured by Roland DG) as a processing machine. The obtained zirconia plastic after machining was fired according to the firing schedules in Tables 2 and 3 using an InFire HTC speed (manufactured by Dents Prisilona Co., Ltd.) as a firing furnace to obtain the zirconia sintered bodies of each example and comparative example.
[0110] The obtained zirconia sintered bodies were evaluated visually by four people according to the following criteria. If three or more of the four people determined that a certain criterion was satisfied, it was determined that the criterion was satisfied. The results are shown in Tables 2 and 3.
[0111] < Evaluation Criteria >
[0112] ○ : No streaks are visible between layers with different yttria content, so there are no issues in the dental clinical evaluation.
[0113] △ : Although there are slight streaks between layers with different yttria content, they are within an acceptable range according to dental clinical evaluation.
[0114] × : Notable streaks are visible between layers with different yttria content, making it unacceptable in clinical evaluation.
[0115] [Evaluation of Strength of Zirconia Sintered Body]
[0116] For each of Examples 1 to 5, Comparative Example 1, and Reference Example 1, the strength was verified by the following method. First, ten rectangular samples of 1.7 mm × 5.2 mm × 20.2 mm were machined from the obtained zirconia plastic block using a DWX-52DC (manufactured by Roland DG) as a processing machine. The obtained zirconia plastic after machining was fired under the conditions of the firing schedule shown in Tables 2 and 3 using an InFire HTC speed (manufactured by Dents Prysilona Co., Ltd.) as a firing furnace. The zirconia sintered after firing was polished with #1000 abrasive paper using a rotary grinder to obtain rectangular sintered samples of 1.2 mm × 4 mm × 14 mm. Using the sintered sample, the 3-point bending strength was measured under conditions of a crosshead speed of 0.5 mm / min and a span of 12 mm in accordance with ISO 6872:2015 (n = 10). The average values of n = 10 are shown in Tables 2 and 3 as evaluation results.
[0117] [Evaluation of ΔE*ab of crown-shaped zirconia sintered bodies]
[0118] For each of the zirconia sintered bodies of Examples 1 to 5 and Comparative Example 1, the color difference ΔE*ab (hereinafter also referred to as "ΔE*") with respect to the zirconia sintered body sintered by the sintering schedule described in Reference Example 1, which is a conventional sintering schedule, was calculated by the following method to confirm the difference in color tone. First, the obtained zirconia plastic block was machined into the shape of an anterior tooth crown using a DWX-52DC (manufactured by Roland DG) as a processing machine. The obtained zirconia plastic after machining was then sintered into samples of the same shape using the sintering schedules described in Tables 2 and 3, respectively, using an InFire HTC speed as the sintering furnace. For the sintered body samples after firing, color measurement was performed using a dental colorimeter (manufactured by Olympus Corporation, 7-band LED light source, "Crystal Eye"), and the lightness, saturation, and color difference ΔE*ab in the L*a*b* color system (JIS Z 8781-4: 2013 Colorimetry - Part 4: CIE 1976 L*a*b* color space) were evaluated at each measurement area of the cervical, body, and in-section (n = 5). The average value of n = 5 is shown in Table 4 as the evaluation result. The color difference ΔE*ab is calculated by the following formula (2) for two sintered body samples obtained with the firing schedules listed in Tables 2 and 3, using the lightness index L* and color coordinates a* and b* in the CIE 1976 L*a*b* color space.
[0119]
[0120] [Evaluation of each physical property value]
[0121] In Examples 1, 3 to 5 and Reference Example 1, the difference in ΔL(WB) values between each layer of the zirconia sintered body was 0.79 to 1.03, and in the evaluation of the aesthetics of the crown-shaped zirconia sintered body, no striations were visible between layers with different yttria content, confirming that there were no issues in the dental clinical evaluation. In addition, in the evaluation of the strength of the zirconia sintered body, the 3-point bending strength of the sintered body sample showed a value equivalent to that of the case where it was fired with a conventional firing schedule (Reference Example 1), indicating strength that was not problematic for dental use. In the evaluation of ΔE*ab of the crown-shaped zirconia sintered body, the color difference ΔE*ab compared to the sample fired with a conventional firing schedule was 2.7 or less.
[0122] In Example 2, the difference in ΔL(WB) values between each layer of the zirconia sintered body was 1.45. In the evaluation of the aesthetics of the crown-shaped zirconia sintered body, although there were slight streaks between layers with different yttria content, they were within an acceptable range for dental clinical evaluation. In the evaluation of the strength of the zirconia sintered body, the 3-point bending strength of the sintered body sample showed a value equivalent to that of a sample fired with a conventional firing schedule, indicating strength that was not problematic for dental use. In the evaluation of ΔE*ab of the crown-shaped zirconia sintered body, the color difference ΔE*ab compared to a sample fired with a conventional firing schedule was 2.7 or less.
[0123] On the other hand, Comparative Example 1 exhibited 3-point bending strength and ΔE* values that were not problematic for dental use, but the difference in ΔL(WB) values between each layer of the zirconia sintered body was 2.7, and in the evaluation of the aesthetics of the crown-shaped zirconia sintered body, striations were noticeable between layers with different yttria content, resulting in an unacceptable outcome in clinical evaluation. As for the cause of the large difference in ΔL(WB) values as in Comparative Example 1, it can be inferred that the sintering schedule involves a temperature range that rises at a constant rate, which affects translucency and color tone. In Patent Document 2 (Japanese Patent Publication No. 2019-524298), as shown in Fig. 3, the sintering profile after 1000°C is a single step, that is, a sintering schedule that rises at a constant rate, so it is believed that the same result as Comparative Example 1 is obtained.
[0124]
[0125]
[0126]
[0127]
[0128] From the above results, it was confirmed that the zirconia sintered body obtained by the manufacturing method of the present invention is desirable as a dental product (e.g., dental prosthesis) in that the occurrence of streaks between layers with different yttria content is suppressed even when the firing time is short. In addition, it was confirmed that the zirconia sintered body obtained by the manufacturing method of the present invention can reproduce the color tone and strength of a dental prosthesis to the same extent as when fired under normal firing conditions (total firing time: 6 to 12 hours), even though it is sintered in a short time.
[0129] Industrial applicability
[0130] The method for manufacturing a zirconia sintered body according to the present invention sinters a zirconia molded body or a zirconia plastic body in a short time, and the resulting zirconia sintered body is useful for manufacturing dental products (dental prostheses, etc.) because it is possible to suppress the occurrence of streaks between layers with different yttria content. In addition, the resulting zirconia sintered body can reproduce the aesthetic requirements (color tone and translucency) and strength of an ideal dental prosthese to the same extent as when sintered under normal sintering conditions, even though it is sintered in a short time. Furthermore, in particular, it is useful as a method for manufacturing dental prostheses such as dentures for anterior teeth because it has excellent color tone and translucency similar to the insulating part of a natural anterior tooth. Explanation of the symbols
[0131] 10: Zirconia plastic P: First off Q: Tadan L: Total length Y: First direction
Claims
Claim 1 The invention has a firing process for firing a zirconia molded body or a zirconia plastic body, wherein the zirconia molded body or the zirconia plastic body comprises a plurality of layers containing a stabilizer, and the plurality of layers include layers with different stabilizer content ratios, and the firing process comprises at least three heating processes, a first heating process (H1), a second heating process (H2), and a third heating process (H3), wherein when the heating rate of the second heating process (H2) is HR2 and the heating rate of the third heating process (H3) is HR3, HR2 = greater than 0 ℃ / min and less than 50 ℃ / min, HR3 = greater than 5 ℃ / min and less than 150 ℃ / min, and HR3 / HR2 > 1, and the starting temperature in each heating process is 1000 ℃ or less in H1, greater than 1250 ℃ and less than 1450 ℃ in H2, and in H3 A method for manufacturing a zirconia sintered body, wherein the temperature is 1450 ℃ or higher and 1550 ℃ or lower, and the temperature reached in each heating process is 1250 ℃ or higher and 1450 ℃ or lower in H1, 1450 ℃ or higher and 1550 ℃ or lower in H2, and 1500 ℃ or higher and 1750 ℃ or lower in H3. Claim 2 A method for manufacturing a zirconia sintered body according to claim 1, wherein when the heating rate of the first heating process (H1) is HR1, HR1 is 40 to 500 ℃ / min. Claim 3 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein the difference in the content of the stabilizer between layers with different content ratios of the stabilizer is 0.1 mol% or more. Claim 4 A method for manufacturing a zirconia sintered body, wherein the stabilizer in claim 1 or 2 is yttria. Claim 5 A method for manufacturing a zirconia sintered body according to claim 4, wherein the content of yttria in all layers of the plurality of layers is 2.5 mol% or more and 7.5 mol% or less with respect to the total mol of zirconia and yttria. Claim 6 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein HR2 is 2 to 30 ℃ / min. Claim 7 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein HR3 is 10 to 100 ℃ / min. Claim 8 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein HR3 / HR2 > 1.
5. Claim 9 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein the maximum sintering temperature in the heating process is 1500 to 1750 ℃ and the holding time at the maximum sintering temperature is within 30 minutes. Claim 10 A method for manufacturing a zirconia sintered body according to claim 9, further comprising a cooling process, wherein in the cooling process, the cooling rate from the maximum firing temperature in the heating process to 800 ℃ is 10 ℃ / min or more. Claim 11 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein the total sintering time from the start of the first heating process (H1) in the sintering process to the end of the holding time at the maximum sintering temperature is within 120 minutes. Claim 12 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein 55% or more of the zirconia molded body or zirconia plastic body is monoclinic. Claim 13 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein at least a portion of the stabilizer is not dissolved in the zirconia in the zirconia molded body or zirconia plastic body. Claim 14 A method for manufacturing a zirconia sintered body according to claim 1 or 2, wherein the zirconia molded body or zirconia plastic body has a predetermined shape of a dental product. Claim 15 A method for manufacturing a zirconia sintered body, wherein the dental product is a dental prosthesis, in accordance with claim 14.
Citation Information
Patent Citations
Zirconia compositions, plasticizers and sintered bodies, and methods for producing them
KR1020190047701A
Tungsten / titania-based composite oxide carrier and method for manufacturing the same, NOX removal catalyst using the carrier, and manufacturing method thereof
KR1020200057155A
Process for producing a dental zirconia article with a fast sintering process
WO2019166938A1
Calcined zirconia object suitable for dentistry
WO2020138316A1
